Research on the Cognitive Changes of Lao Society on China-Laos Railway - LORVANXAY, AM (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study investigates the evolving attitudes of Lao citizens toward the Lao-China Railway, from its planning and construction phases to its current operation, highlighting its multifaceted impact on Lao society. A set of interview-based questions was used to collect data from participants across nine occupational groups. The data were analyzed using qualitative descriptive methods. The study found that the Lao-China Railway is widely regarded by local stakeholders as a transformative project with the potential to stimulate economic growth, improve connectivity, and create new opportunities. However, across all groups workers, merchants, service providers, industrial owners, farmers, tour guides, students, teachers, and government officials there are shared concerns about equitable access to benefits and the risk of being overshadowed by more experienced or better-equipped foreign actors. Local workers hoped for employment opportunities but were concerned that high-skilled and well-paid jobs would largely go to Chinese workers due to a lack of technical skills and experience. Merchants appreciated easier access to Chinese markets but feared intense competition. Service providers expected increased customer demand, especially in tourism, yet worried about meeting international standards. Industrial owners saw potential in reduced logistics costs but were concerned about competing with large foreign companies. Farmers viewed the railway as a chance to export products but were uncertain about meeting quality and safety requirements. Tour guides welcomed more tourists but feared being sidelined by foreign tour operators. University students hoped for new career paths but felt unprepared for a competitive job market. Teachers and civil servants emphasized the need for education reform and stronger governance to meet future demands.